Implicated reading: a method for reflecting on practice. Issue 3 (4th May 2017) - Harrison, Michaela J.
Abstract: This paper evaluates an attempt by the author to operationalise the theory of reflective practice within the context of initial teacher education. Whilst an integral element of many teacher education programmes, the problematic of 'how' to reflect on practice remains a concern. In response, and taking inspiration from the work of Deleuze and Guattari, specifically their critique of representational thought and common understandings of text, the author experiments with a method for reflecting called implicated reading. The method involves the reading of students' lived experiences as beginning teachers (recorded in written form), against a variety of other texts. The author draws on interview data to analyse and discuss the merits of the approach. The paper concludes that the method of implicated reading has the potential to unsettle the common tendency to focus on meaning and interpretation when reflecting on events and experiences. It is argued that the student teachers involved in the project instead begin to experience reflection as a process of connectivity, rethinking pedagogy as a result.